2018
DOI: 10.1111/jvh.12908
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of serum HBV‐RNA in chronic HBV infection

Abstract: Virus-like particles encapsulating HBV-RNA represent a serum biomarker for assessing viral replication activity in clinical practice. However, baseline levels of serum HBV-RNA and their associations with viral replicative intermediates and liver disease in phases of chronic hepatitis B remain unknown. In this cross-sectional study, 102 patients were categorized into immune-tolerant (IT), HBeAg-positive immune active (HBeAg+IA), inactive carrier (IC) and HBeAg-negative immune active (HBeAg-IA) phases. HBV-RNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
79
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 36 publications
7
79
0
Order By: Relevance
“…Huang et al reported that serum HBV pgRNA weakly correlated with cccDNA in untreated CHB patients with a correlation coefficient of 0.363 ( P < 0.001), which is similar to the result of Gao et al ( r = 0.25, P < 0.01), who quantified serum polyadenylated HBV RNA by RACE–quantitative PCR . In a CHB natural history study, Wang et al found a moderate overall correlation between serum 3.5‐kb RNA and intrahepatic cccDNA ( r = 0.596, P < 0.001) among all of the recruited patients; however, when classifying the patients into immune‐tolerant, HBeAg‐positive immune active, inactive carrier, and HBeAg‐negative immune active phases, the correlation disappeared in all phases . For patients under NA treatment, Wang et al found no significant correlation between serum HBV RNA and cccDNA copy numbers .…”
Section: Correlation Between Serum Hbv Rna and Other Hbv Markerssupporting
confidence: 62%
See 2 more Smart Citations
“…Huang et al reported that serum HBV pgRNA weakly correlated with cccDNA in untreated CHB patients with a correlation coefficient of 0.363 ( P < 0.001), which is similar to the result of Gao et al ( r = 0.25, P < 0.01), who quantified serum polyadenylated HBV RNA by RACE–quantitative PCR . In a CHB natural history study, Wang et al found a moderate overall correlation between serum 3.5‐kb RNA and intrahepatic cccDNA ( r = 0.596, P < 0.001) among all of the recruited patients; however, when classifying the patients into immune‐tolerant, HBeAg‐positive immune active, inactive carrier, and HBeAg‐negative immune active phases, the correlation disappeared in all phases . For patients under NA treatment, Wang et al found no significant correlation between serum HBV RNA and cccDNA copy numbers .…”
Section: Correlation Between Serum Hbv Rna and Other Hbv Markerssupporting
confidence: 62%
“…(33) In a CHB natural history study, Wang et al found a moderate overall correlation between serum 3.5kb RNA and intrahepatic cccDNA (r = 0.596, P < 0.001) among all of the recruited patients; however, when classifying the patients into immune-tolerant, HBeAg-positive immune active, inactive carrier, and HBeAg-negative immune active phases, the correlation disappeared in all phases. (52) For patients under NA treatment, Wang et al found no significant correlation between serum HBV RNA and cccDNA copy numbers. (21) In addition, Gao et al reported that serum HBV polyA RNA had no correlation with intrahepatic cccDNA at 96 weeks after NA treatment.…”
Section: Correlation With Cccdna and Other Viral Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum HBV RNA levels correlate to intrahepatic pgRNA, liver histopathology, and cccDNA, supporting a potential utility for serum pgRNA in indirectly monitoring cccDNA activity during NA treatment. However, the use of this marker during NA treatment in predicting clinical outcomes remains undemonstrated, although the following model of pgRNA utility during NA treatment could be extrapolated: a subject with undetectable HBV DNA but consistently elevated pgRNA presumably has active cccDNA transcription occurring (Fig.…”
mentioning
confidence: 86%
“…In addition, other studies have also suggested that nucleocapsid maturation may not be dependent on DNA synthesis . Similar to the production of Dane virion, the nucleocapsid‐packaged pgRNA may also be enveloped and released from hepatocytes to produce pgRNA virion (Figure ), but its infectivity requires extensive experimental evidence.…”
Section: Pgrna Encapsidation and Reverse Transcriptionmentioning
confidence: 99%